HISTORICAL AND ETHNOGRAPHIC ANALYSIS OF TRADITIONAL FARMING PRACTICES AND AGRICULTURAL TOOLS IN KARAKALPAKSTAN (TAMADDUN NURI JURNALI, 2025)
This article primarily analyzes the experiences of Karakalpak farmers, their methods of land cultivation, and their labor tools from a historical and ethnographic perspective. Additionally, it comparatively illustrates the diversity of tools and the similarities in agricultural implements used by neighboring peoples. Changes in certain labor tools are presented using examples from field notes.